UPAYA PENYELENGGARAAN PEMERINTAHAN YANG BAIK (GOOD GOVERNANCE) DALAM PENCEGAHAN KORUPSI, KOLUSI DAN NEPOTISME - Fransiska NG Purba; M. Mun’am Syaiful Huda (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
The government is often not as good and not yet as expected in using its authority, especially in the implementation of community services, as for a number of uses of state administrative law to realize the government's implementation and of course it is necessary for the community, including the normatife, this utilityIt is a structural principle, and the utility of legal guarantees to create a sound and clean governance order that conforms to the principles adopted in the state of law. And the increasing regulation of the AUPB principle created a strong momentum, at which time the administrative law was enacted in 2014, as a result of the follow-up of the statewide draft so the state has a need to agree on public welfare, one of which is public service. This method of research is quality assessment.The principles of good governance are usually carried out in the framework of clean government of corruption, collusion, and nepotism, obstacles to the implementation of good governance principles and efforts to implement good governance principles. The implementation of good government must be based on the general principles or guidelines of government to be better and clearly stipulated in article 10 of law number 30 of 2014 concerning government administration, and service services must be based on invitation and legality legislation.